Standalone immersion cooling for high performance servers - Low, Philip Jun Xiang (Nanyang Technological University, 2022)
The study is to develop and addresses the problem that present data centers faces which are still utilizing air conditioning as a medium to cool the server racks. The study will focus on immersion cooling as a cooling alternative medium to remove heat from the high-performance servers. By proving immersion cooling is more efficient than air cooling, it could transform the data centers to a more economical industry. The experiment was carried out with a single motherboard server, liquid coolant, Novec 649 and a circulator unit to alter the temperature of the water in the condenser coil. The components are built and installed inside an enclosed tank to facilitate everlasting loop of condensation and evaporation. Additionally, a data acquisition unit and a thermocouple were used to measure the liquid temperature in the tank. The experiment utilizes two-phase immersion cooling method and alteration of parameters which includes central processing unit (CPU) load and condenser temperature to fathom the effects of cooling. Further, the experiment will include a submersible pump to induce forced convection to study the hypothesis of forced convection is more efficient than natural convection. The results showed under the influence of forced convection, the temperature of the CPUs have gradually decreased by a range of 3-8℃. Moreover, the result on heat transfer coefficient calculations have shown both upwards and downwards trend for different condenser temperature under natural convection while forced convection only experienced a downward trend of heat transfer coefficient. These results have displayed the importance of different operating condition environment would influence the performance of the experiment. Future works were also proposed to enhance the two-phase immersion cooling which includes exploring new coolant that are more economical and efficient, and a submersible pump that can adjust the pump flow for data collection purposes.